Exploring Glucagon‐Like Peptide‐1 Receptor Agonists Usage Among Non‐Diabetic Healthcare Providers: A Cross‐Sectional Multi‐Country Study - Abdulqadir J. Nashwan (11659453) (2025)
Background and Aim Glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) were initially developed for type 2 diabetes but have gained widespread use for weight management, including among non‐diabetic individuals. This study aimed to estimate the prevalence of GLP‐1RA use, describe usage patterns, and explore healthcare providers' (HCPs) perceptions of their efficacy and safety. Methods A cross‐sectional study was conducted among 657 HCPs from 10 countries using a structured online survey between September and December 2023. Convenience sampling was employed, statistical analyses were performed using STATA 17. Associations between demographic characteristics and perceptions of GLP‐1RAs were analyzed using the chi‐square test. Results Among 657 HCPs, 59.2% were female and 40.8% were male, with a median age of 36.0 years (IQR: 29.0–44.0) and a median BMI of 26.7 (IQR: 23.8–30.7). Among professional groups, nurses accounted for 44.7%, followed by physicians (36.2%) and allied health professionals (18.7%). Semaglutide (45.7%, 95% CI: 41.8%−49.5%) was the most commonly used GLP‐1RA, followed by Liraglutide (36.9%, 95% CI: 33.2%−40.8%). Other GLP‐1RAs were used less frequently, including Dulaglutide (17.0%, 95% CI: 14.2%−20.1%), Exenatide (14.1%, 95% CI: 11.5%−17.0%), Albiglutide (7.0%, 95% CI: 5.1%−9.2%), and Lixisenatide (8.5%, 95% CI: 6.5%−10.9%. Regarding perceived safety, 68.6% considered GLP‐1RAs safe. Safety perceptions were significantly associated with educational level (p = 0.022), with participants holding higher degrees being more likely to perceive GLP‐1RAs as unsafe (18.3%) compared to those with a bachelor's degree or lower (10.8%). No associations were found with age (p = 0.487), sex (p = 0.729), or BMI (p = 0.089). Similarly, 73.5% of participants considered GLP‐1RAs effective for perceived efficacy. No associations were found with sex (p = 0.663) or BMI (p = 0.446). Older participants (p = 0.011) and those with higher education (p = 0.006) were more likely to perceive GLP‐1RAs as ineffective. Conclusion This study provides the first prevalence estimate of GLP‐1RA use among HCPs and GLP1‐Ras users and explores the associations between demographic characteristics and perceptions of safety and efficacy. The findings highlight the self‐prescribing practices of these medications for weight management and underscore the need for appropriate monitoring to avoid potential health risks. Other Information Published in: Health Science Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/hsr2.70638